2014
DOI: 10.1128/jcm.01629-14
|View full text |Cite
|
Sign up to set email alerts
|

The β-Lacta Test for Direct Detection of Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae in Urine

Abstract: cWith the ␤-Lacta test, production of extended-spectrum ␤-lactamases (ESBLs) was assayed in 200 urine samples showing Gramnegative bacilli during direct microscopic examination. While 168 samples tested negative, all samples yielding ESBL-producing Enterobacteriaceae after culture gave positive (n ‫؍‬ 30) or uninterpretable (n ‫؍‬ 2) results. The sensitivity and specificity of ESBL detection were 94% and 100%, respectively. A survey conducted from 2002 to 2010 by the French national infection control program d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
(15 reference statements)
3
17
0
1
Order By: Relevance
“…Our results are consistent with published data with respect to the low sensitivity of BLT in the detection of plasmid-encoded (CMY, DHA) or overproduced AmpC -lactamases(10,11). In contrast, K. oxytoca isolates with high-level expression of their chromosome-encoded β-lactamase were previously reported as being BLT-positive(10). This discrepancy may be explained by a difference in -lactam hydrolysis rates of OXY-1 and OXY-2 (15) which have not been determined.…”
supporting
confidence: 95%
“…Our results are consistent with published data with respect to the low sensitivity of BLT in the detection of plasmid-encoded (CMY, DHA) or overproduced AmpC -lactamases(10,11). In contrast, K. oxytoca isolates with high-level expression of their chromosome-encoded β-lactamase were previously reported as being BLT-positive(10). This discrepancy may be explained by a difference in -lactam hydrolysis rates of OXY-1 and OXY-2 (15) which have not been determined.…”
supporting
confidence: 95%
“…The BLT showed interesting intrinsic diagnostic performance in laboratory evaluations, notably sensitivity and specificity >95% for ESBL detection on Enterobacteriaceae colonies [1417]. However, to our knowledge, a BLT-guided antimicrobial adaptation strategy has never been investigated in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods are rapid and simple and allow direct assessment of clinical samples (Dortet et al, 2014a(Dortet et al, , 2014bGallah et al, 2014), their visual interpretation may give rise to ambiguity across different microbiology laboratories (Maurer et al, 2015;Simner et al, 2014;Tijet et al, 2013). Simner et al (2014) reported that the degree of color change used to determine positive results varied, while Tijet et al (2013) reported that intermediate color changes caused discrepancies between the interpretations of the findings made by 2 different laboratories.…”
Section: Discussionmentioning
confidence: 95%